Associations of dietary antioxidant micronutrients with the prevalence of obesity in adults - Yang, Yazhu; Xu, Haifeng; Zhang, Yi; Chen, Lin; Tian, Chengzi; Huang, Bihui; Chen, Youpeng; Ma, Lin (Frontiers in Nutrition, 2023)
Background: Antioxidant micronutrients are an essential supplemental therapeutic alternative for the treatment of obesity in clinical.NO research, however, has examined the connection between the complexity level of dietary antioxidants and obesity. Materials and Methods:We mainly aimed to investigate the relationship between a combination of antioxidants and obesity using the database of the national health and nutrition examination survey (NHANES). This cross-sectional study contains the survey of 41021 people (≥18 years) in total ranging from 2005 to 2018. Multivariate logistic and weighted quantile sum (WQS) regression were performed to investigate the associations between these antioxidants, both individually and collectively, and the prevalence of obesity. The restricted cubic spline (RCS) regression was also utilized to analyze the linearity of these associations. Results: According to multivariate logistic models, we found that the levels of most antioxidants in the highest quartile were independently related to a lower prevalence of obesity, while a reverse result was observed in selenium (P for trend < 0.05). The WQS index revealed that a total of the 11 antioxidants is negatively related to the prevalence of obesity and abdominal obesity (all P<0.001), and iron (weight= 40.20%) has the greatest contribution to the combined effect of obesity. In addition, the RCS regression showed that retinol, vitamin A, α-carotene, β-carotene, β-cryptoxanthin, vitamin C, iron and copper all had a non-linear association with obesity. Threshold effect analysis demonstrated that the inflection points of retinol, vitamin A, α-carotene, β-carotene, β-cryptoxanthin, vitamin C, iron, and cooper were 235.57, 374.81, 58.89, 891.44, 30.70, 43410.00, 11240.00 and 990.00 μg/day, respectively. Conclusion: Our study found that a high level of a complexity of 11 dietary antioxidants is related to a lower prevalence of obesity, among which iron and vitamin C make the biggest contribution to obesity.